CONSONANT GEMINATES IN SIMALUNGUN LANGUAGE - Luh Anik Mayani (Linguistik Indonesia, 2017)
This study aims to describe morphophonemic processes which result in consonant geminates as well as to classify types of consonant geminates in Simalungun language. Types of geminates in this study are analyzed from the morphophonemic processes resulted in consonant geminates and from the true or fake types of geminates. The data analyzed in this paper is collected during a short fieldwork in Pematang Raya Kecamatan Raya (Raya district), Simalungun regency, Sumatra Utara Province. From the analysis, it can be concluded that consonant geminates in Simalungun language always occur word-medially. Consonant geminates found in this language are [pp], [tt], [kk], [ss], [ll], [gg], [nn] and [mm]. Based on the morphophonemic processes, geminates in Simalungun language can be divided into four types: (1) consonant geminates resulted from assimilation of a nasal to a following homorganic stop, (2) consonant geminates resulted from velarization and assimilation, (3) assimilation of heterorganic consonant clusters and (4) nasal geminates. Regarding true and fake type of geminates, true geminates in Simalungun are found morpheme-internally or lexicalized; fake geminates are resulted from affixation and clitization. True geminates in Simalungun are [pp], [tt], [ss], [kk], [gg] and [mm], while the fake geminates found in this language are [ss], [kk], [ll] and [nn].